Historical memory preserving of the Great Patriotic war in modern patriotic projects of student youth - Miziurova E. I. (University as a factor of Modernization of Russia: History and Prospects (to the 55th anniversary of the I.N. Ulyanov ChSU), 2024)
patriotic education of students is one of the main directions in the educational work of Vavilov University. The author of the article points out that in order to educate young people in civic qualities, it is necessary to study the heroic past of their country, to cultivate respect for the courage of its people, for the memory of the victims. That is why the theme of the Great Patriotic War is relevant and in demand among young people.
Keywords: историческая память; патриотическое воспитание; historical memory; patriotic education; современная молодежь; составляющие патриотизма; патриотический проект; modern youth; components of patriotism; patriotic project